Ameliorative effect of biofabricated ZnO nanoparticles of Trianthema portulacastrum Linn. on dermal wounds via removal of oxidative stress and inflammation. Issue 38 (13th June 2018) - Yadav, Ekta; Singh, Deepika; Yadav, Pankajkumar; Verma, Amita
Abstract : The curative efficacy of a green synthesized zinc oxide nano-ointment on wound healing was investigated. Abstract : An impediment in the process of wound healing can be attributed to reactive oxygen species and inflammation. The curative efficacy of green synthesized Trianthema portulacastrum Linn. zinc oxide nanoparticles (ZnOTP) was investigated in the present study for evaluation of their wound healing potential in rodents. Total phenolic and flavonoid content of ZnOTP was determined, and antioxidant potential was evaluated by the DPPH method. In vitro anti-inflammatory activity of ZnOTP was evaluated by membrane stabilization and albumin denaturation, along with proteinase inhibitory assays. The synthesized ZnOTP were characterized by UV-Visible spectroscopy, Fourier transform infrared (FT-IR) studies, Field Emission Scanning Electron Microscopy (FESEM) and Energy Dispersive X-ray (EDX) studies. The wound healing potential of ZnOTP was monitored by excision and incision wound models. Analyses confirmed the formation of spherical nanoparticles of 10–20 nm size along with strong signals of zinc and oxygen atoms. Significant results ( p < 0.05) of wound contraction rate, epithelialization and histopathology of the healed tissues of rats confirmed the promising wound healing property of ZnOTP. In addition, inflammatory markers, biochemical estimation such as the hydroxyproline content of granulation tissue, and the profile of antioxidant enzymes also supported the wound healing potential of ZnOTP. The present study advocated the attenuation of wounds via antioxidant and anti-inflammatory activities of a green synthesized nano-ointment.